Association of TPH1 with suicidal behaviour and psychiatric disorders in the Chinese population. Issue 2 (7th February 2006) - Liu, X; Li, H; Qin, W; He, G; Li, D; Shen, Y; Shen, J; Gu, N; Feng, G; He, L
Abstract : Tryptophan hydroxylase (TPH), the rate limiting enzyme in serotonin biosynthesis, is one of the most important regulating factors in the serotonergic system. Recently, polymorphisms of the TPH gene have been identified as being associated with suicide, but the evidence is inconsistent. To investigate the role in suicide of one of the isoforms, TPH1, we examined the association of five single nucleotide polymorphisms (SNPs) in the promoter region and in intron 7 of the TPH1 gene based on a sample from the Chinese population of 810 subjects, of whom 329 had made no suicide attempts (NSA), 297 had made suicide attempts (SA), and 184 were healthy subjects (HS). In this study, we observed statistically significant differences between NSA and HS subjects in allele distributions on one marker, −6526A (p = 0.0329; odds ratio (OR) 1.36; 95% confidence interval (CI) 1.01 to 1.81). No significant difference in genotype distribution or allele frequencies of other polymorphisms was found between the suicide victims and the controls. The overall haplotype frequency was significantly different between cases and healthy controls (p = 0.000024 NSA v HS; p<0.000001, SA v HS; p<0.000001, cases v HS). We found the haplotype TCAAA of −7180/−7065/−6526/218/779 to be strongly associated with suicidal behaviour and psychiatric disorders (p = 0.00243; OR = 1.62; 95% CI 1.17 to 2.24 and p = 0.018; OR = 1.41; 95% CI 1.05 to 1.91), which suggests an association of TPH1 with suicidal behaviour and indicates that TPH1 may play a significant role in the aetiology of psychiatric disorders in the Han Chinese population.